Applications of physiological ecology to forest management - Landsberg, J. J. (Physiological ecology., 1997)
Forest management is a complex process that now incorporates information obtained from many sources. It is increasingly obvious that the physiological status of the trees in a forest has a dramatic impact on the likely success of any particular management strategy. Indeed, models described in this book that deal with forest productivity and sustainability require physiological information. This information can only be obtained from an understanding of the basic biological mechanisms and processes that contribute to individual tree growth. This valuable book illustrates that physiological ecology is a fundamental element of proficient forest management. * Provides essential information relevant to the continuing debate over sustainable forest management * Outlines how modern tools for physiological ecology can be used in planning and managing forest ecosystems * Reviews the most commonly used forest models and assesses their value and future.